EXPLAINING COORDINATION BETWEEN NATIONAL REGULATORS IN EU AGENCIES: THE ROLE OF FORMAL AND INFORMAL SOCIAL ORGANIZATION. (19th November 2015) - HEIMS, EVA M.
Abstract : Coordination between national regulators in EU agencies is based on a variety of mechanisms – such as mutual exchange and hierarchy – which the existing literature has extensively documented. However, it has paid less attention to explaining such variation. This article suggests that cultural theory can systematically integrate the observation of varied coordination mechanisms into one framework. More crucially, cultural theory also provides a coherent theoretical explanation for variation of coordination mechanisms by pointing to the importance of formal and informal social organization: the grid and group boundedness of national regulators, namely the constraints exercised on them by EU bodies and by the shared norms of their professional communities, can account for the emergence of different types of coordination across policy sectors. The article demonstrates this by presenting original empirical research on three cases, namely coordination between national regulators in the EU agencies responsible for food and maritime safety, as well as banking regulation.